Pengembangan Pemasaran Tanaman Obat Keluarga Sebagai Produk Unggulan Ning’s Kitchen Garden Melalui Pendekatan Ekonomi Kreatif: Pengabdian - Nila Rusyanti; Zandra Singal, Rachel; Maharani Abdul, Kartini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to examine the implementation of creative economic activities through the marketing of Family Medicinal Plants (TOGA) as a flagship product at Ning's Kitchen Garden. Indonesia possesses great potential in developing medicinal plants based on local biodiversity, where the cultivation of TOGA can provide health benefits and economic opportunities for families. Ning's Kitchen Garden in Tanjung Selor, Bulungan, is a creative economy-based business unit focused on the independent and sustainable cultivation of TOGA, utilizing the home yard optimally. The creative economy approach in this business is realized through product innovation and diversification. Simple gardening activities are transformed into productive activities with added economic value. The products generated are not only whole TOGA but also high-value processed goods, such as healthy herbal drinks (smoothies and modern packaged herbal drinks/jamu), as well as other processed foods like sourdough bread and vegetable salads with added herbs. This innovation combines traditional knowledge with a modern approach, allowing the products to be accepted by the broader market. In addition to product innovation, Ning's Kitchen Garden also implements a sustainable organic farming system (sustainable agriculture) without chemical pesticides, using fertilizer made from kitchen waste. This initiative supports local food self-sufficiency and the empowerment of women as agents of change in family food security